Millimetre Wave response of alpha-(BEDT-TTF)(2)NH4Hg(SCN)(4) - Ardavan, A; Singleton, J; Hayes, W; Polisski, A; Goy, P; Kurmoo, M; Day, P (1997)
We present the results of a study of the millimetre-wave response of the organic metal alpha-(BEDT-TTF)(2)NH4Hg(SCN)(4), between 500 mK and 4.2 K and in magnetic fields of up to 17 T. Two relatively broad features are interpreted as a two dimensional (2D) cyclotron resonance (CR) with a CR mass m(2D)(CR) = 1.35 +/- 0.1 m(e), and a 1D CR with CR mass m(1D)(CR) = 0.85 +/- 0.05 m(e). Conduction electron spin resonance and magnetic quantum oscillations are also observed. Analysis of the quantum oscillations yields an effective mass of m(RF)* = 2.7 +/- 0.2 m(e).